Selective Aerobic Oxidation of 5‐Hydroxymethylfurfural to 2, 5‐Diformylfuran or 2‐Formyl‐5‐furancarboxylic Acid in Water by using MgO⋅CeO2 Mixed Oxides as Catalysts. Issue 8 (6th April 2018) - Ventura, Maria; Lobefaro, Francesco; de Giglio, Elvira; Distaso, Monica; Nocito, Francesco; Dibenedetto, Angela
Abstract: Mixed oxides based on MgO⋅ CeO2 were used as efficient catalysts in the aerobic oxidation of 5‐hydroxymethylfurfural (5‐HMF) to afford, with very high selectivity, either 2, 5‐diformylfuran (DFF, 99 %) or 2‐formyl‐5‐furancarboxylic acid (FFCA, 90 %), depending on the reaction conditions. 5‐Hydroxymethyl‐2‐furancarboxylic acid (HMFCA, 57–90 %) was formed only at low concentration of 5‐HMF (<0.03 m ) or in presence of external bases. The conversion of 5‐HMF ranged from a few percent to 99 %, according to the reaction conditions. The oxidation was performed in water, with O2 as oxidant, without any additives. The surface characterization of the catalysts gave important information about their acid–base properties, which drive the selectivity of the reaction towards DFF. FFCA was formed from DFF at longer reaction times. Catalysts were studied by XPS and XRD before and after catalytic runs to identify the reason why they undergo reversible deactivation. XRD showed that MgO is hydrated to Mg(OH)2, which, even if not leached out, changes the basic properties of the catalyst that becomes less active after some time. Calcination of the recovered catalyst allows recovery of its initial activity. The catalyst is thus recoverable (>99 %) and reusable. The use of mixed oxides allows tuning of the basicity of the catalysts, avoiding the need for external bases for efficient and selective conversion of 5‐HMF and waste formation, resulting in an environmentally friendly, sustainable process. Abstract : Mixology : By using a tunable mixed oxide, such as MgO⋅ CeO2, selective and quantitative oxidation of 5‐hydroxymethylfurfural (5‐HMF) to 2, 5‐diformylfuran (DFF) or 2‐formyl‐5‐furancarboxylic acid (FFCA) is carried out in water in the presence of O2 as oxidant. Interestingly, the oxidation of the aldehyde moiety, which brings about the formation of 5‐hydroxymethyl‐2‐furancarboxylic acid (HMFCA), can be suppressed.